2011
DOI: 10.1111/j.1750-2659.2011.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 2009 pandemic influenza A(H1N1) virus Infection in different age groups by using rapid influenza diagnostic tests

Abstract: Please cite this paper as: Gao et al. (2011) Detection of 2009 pandemic influenza A(H1N1) virus Infection in different age groups by using rapid influenza diagnostic tests. Influenza and Other Respiratory Viruses 6(3), e30–e34. Background  The performance of rapid influenza diagnostic tests (RIDTs) in detecting influenza A(H1N1) 2009 has varied widely. Evaluations of RIDTs among infected individuals across all age groups have not been described in depth. Objectives  Determine RIDT clinical sensitivity in compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 13 publications
(28 reference statements)
1
19
1
Order By: Relevance
“…We were unable to compare the RIDT performance among specimen types because the specimens included in this study were all throat swabs. Although data show that RIDT sensitivity decreases significantly with increasing age,19 no significant differences were found among children of varying age in our study. Our results are consistent with other studies that have found children with H1N1 and negative RIDT to have lower viral loads compared to those with positive RIDT 20…”
Section: Discussioncontrasting
confidence: 94%
“…We were unable to compare the RIDT performance among specimen types because the specimens included in this study were all throat swabs. Although data show that RIDT sensitivity decreases significantly with increasing age,19 no significant differences were found among children of varying age in our study. Our results are consistent with other studies that have found children with H1N1 and negative RIDT to have lower viral loads compared to those with positive RIDT 20…”
Section: Discussioncontrasting
confidence: 94%
“…The emergence of a variant virus in 2009 highlighted the need to evaluate the reactivity of RIDTs as the NP from influenza A(H1N1)pdm09 originated from swine rather than human viruses 5 . Reduced reactivity of RIDTs with influenza A(H1N1)pdm09 in comparison with seasonal influenza viruses 6–10 is of public health concern. Rapid influenza diagnostic tests were found to be capable of detecting influenza A(H1N1)pdm09 in respiratory specimens, but many infections could be missed, especially in specimens with low viral loads 10…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were observed in the US; clinicians were less likely to provide anti-influenza agents to adults ≥65 years old with influenza, compared with younger adults [15]. The low oseltamivir utilization in elderly may be explained by atypical presentation in this age group and/or decreased sensitivity of rapid influenza diagnostic testing [16-18]. The use of rapid diagnostic tests would ensure oseltamivir were only prescribed to people with confirmed influenza, reducing inappropriate use [18].…”
Section: Discussionmentioning
confidence: 59%
“…The use of rapid diagnostic tests would ensure oseltamivir were only prescribed to people with confirmed influenza, reducing inappropriate use [18]. However, reliance on typical influenza symptoms and rapid influenza diagnostic tests for clinical decision-making may lead to many influenza infections going untreated or causing a treatment delay [16]. A global pooled analysis showed the relative risk of death was highest in the age groups 50–64 and ≥65 years and the presence of chronic illness increased the likelihood of death [17].…”
Section: Discussionmentioning
confidence: 99%